Examining changes in personality disorder and symptomology in an adolescent sample receiving intensive mentalization based treatment: a pilot study - Kirsten Hauber; Albert Eduard Boon; Robert Vermeiren (BMC, 2017)
Abstract Objective To examine changes in personality disorders and symptomology and the relation between personality disorder variables and treatment outcomes in an adolescent sample during partial residential mentalization based treatment. Methods In a sample of 62 (out of 115) adolescents treated for personality disorders, assessment was done pre- and post-treatment using the Structured Clinical Interview for DSM personality disorders and the Symptom Check List 90. Results Significant reductions in personality disorder traits (t = 8.36, p = .000) and symptoms (t = 5.95, p = .000) were found. During pre-treatment, 91.8% (n = 56) of the patients had one or more personality disorders, compared to 35.4% (n = 22) at post-treatment. Symptom reduction was not related to pre-treatment personality disorder variables. Conclusion During intensive psychotherapy, personality disorders and symptoms may diminish. Future studies should evaluate whether the outcomes obtained are the result of the treatment given or other factors.